Reasons for inconsistent condom use by young adults in Mahalapye, Botswana - Luhaka Kanda; Robert Mash (AOSIS, 2018)
Background: Botswana is one of the countries significantly affected by the HIV and AIDS epidemic. Despite an extensive preventive campaign, the incidence of HIV remains high.Condoms are an important contributor to prevention of new HIV infections, although they are not consistently used by young adults. Aim: The aim of this study was to explore the reasons why condoms are not consistently usedby young adults. Setting: Mahalapye District Hospital and Airstrip Clinic, Botswana. Method: This was a phenomenological qualitative study using individual in-depth interviews.Eleven participants were purposively selected, including six males and five females. Data were transcribed and analysed using the framework method. Results: All participants acknowledged the importance of utilising condoms to prevent unplanned pregnancies and sexually transmitted infections. Reasons not to use condoms were a need to have a child,implied lack of trust or faithfulness, long-term relationships need to please the partner and decreased pleasure. Other contributing factors were lack of knowledge of benefits, less fear of contracting HIV and AIDS as it can now be controlled with medication,influence of tradition, alcohol and drug abuse, peer pressure, power and gender issues and the refusal of the partner. The female condom was largely rejected by young adults in general and by women in particular because of its size and the perception that it is complicated to insert. Conclusion: The current preventive campaign against HIV and AIDS needs to take cognisance of the factors affecting decisions on the use of condoms by young adults and the obstacles to their use, particularly the new belief that HIV and AIDS is no longer a significant concern.